The Manifestations Of The Formal Approach Of Qudama Bin Jaafar In His Book Criticism Of Poetry - sakou, mohamed (El Omda in Linguistics and Discourse Analysis, 2025)
Perhaps one of the most famous scientific and literary figures known for its scientific achievement and distinguished position among the critics and theorists of that era,the great critic Qudama bin Jaafar d. Which made critics after him classify Qudama's efforts in the category of distinction and uniqueness, especially in the theoretical and purely formal aspects. In this article, we will address a number of critical opinions, new concepts and terms that we consider worthy of research, clarification and discussion. Especially all that is related to Qudamah approach and its valuable additions to the critical process.